Richter transformation driven by Epstein–Barr virus reactivation during therapy‐related immunosuppression in chronic lymphocytic leukaemia. Issue 1 (30th March 2018) - García‐Barchino, Maria J; Sarasquete, Maria E; Panizo, Carlos; Morscio, Julie; Martinez, Antonio; Alcoceba, Miguel; Fresquet, Vicente; Gonzalez‐Farre, Blanca; Paiva, Bruno; Young, Ken H; Robles, Eloy F; Roa, Sergio; et al.
Abstract: The increased risk of Richter transformation (RT) in patients with chronic lymphocytic leukaemia (CLL) due to Epstein–Barr virus (EBV) reactivation during immunosuppressive therapy with fludarabine other targeted agents remains controversial. Among 31 RT cases classified as diffuse large B‐cell lymphoma (DLBCL), seven (23%) showed EBV expression. In contrast to EBV – tumours, EBV + DLBCLs derived predominantly from IGVH ‐hypermutated CLL, and they also showed CLL‐unrelated IGVH sequences more frequently. Intriguingly, despite having different cellular origins, clonally related and unrelated EBV + DLBCLs shared a previous history of immunosuppressive chemo‐immunotherapy, a non‐germinal centre DLBCL phenotype, EBV latency programme type II or III, and very short survival. These data suggested that EBV reactivation during therapy‐related immunosuppression can transform either CLL cells or non‐tumoural B lymphocytes into EBV + DLBCL. To investigate this hypothesis, xenogeneic transplantation of blood cells from 31 patients with CLL and monoclonal B‐cell lymphocytosis (MBL) was performed in Rag2 –/– IL2γc –/– mice. Remarkably, the recipients' impaired immunosurveillance favoured the spontaneous outgrowth of EBV + B‐cell clones from 95% of CLL and 64% of MBL patients samples, but not from healthy donors. Eventually, these cells generated monoclonal tumours (mostly CLL‐unrelated but also CLL‐related), recapitulating the principal features of EBV + DLBCL in patients. Accordingly, clonally related and unrelated EBV + DLBCL xenografts showed indistinguishable cellular, virological and molecular features, and synergistically responded to combined inhibition of EBV replication with ganciclovir and B‐cell receptor signalling with ibrutinib in vivo . Our study underscores the risk of RT driven by EBV in CLL patients receiving immunosuppressive therapies, and provides the scientific rationale for testing ganciclovir and ibrutinib in EBV + DLBCL. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.